Study on the Morphology, Wear Resistance, and Corrosion Resistance of CuSn12 Alloys Subjected to Machine Hammer Peening - Ning Nie; Lu Yu; Shouwei Xu; Qiyuan Tian; Chenchen Ding; Lihong Su; Hui Wang (Metals)
In this study, machine hammer peening (MHP) was employed to enhance the surface properties of CuSn12 alloys, and the effects of different impact energies on the surface morphology, mechanical properties, and electrochemical properties were systematically investigated. The results revealed that the surface morphology evolution after MHP treatment exhibited unique non-monotonic characteristics, which significantly differed from the surface effects of conventional shot peening technology. Microhardness tests indicated that the surface hardness increased by 40% to approximately 150 HV after treatment with 3.5 J impact energy. Friction and wear tests demonstrated that specimens treated with 2.7 J impact energy exhibited optimal wear resistance, with an 82.7% reduction in volume wear loss, and the wear mechanism transformed from composite wear to mild fatigue wear. Electrochemical performance tests showed that corrosion resistance continuously improved as the impact energy increased from 2.7 J to 3.5 J, primarily attributed to grain refinement and passive film formation; however, treatment with 1.7 J impact energy resulted in decreased corrosion resistance. The results demonstrate that optimizing MHP process parameters can significantly enhance the overall properties of CuSn12 alloys, providing a novel technical approach for the surface-strengthening of this alloy.